Social cognition and behavior, in relation to executive and other cognitive functionsin patients with schizophrenia and bipolar affective disease – a comparative case study - Krukow, Paweł; Karakuła, Hanna (Current Problems of Psychiatry, 2012)
Aim: The aim of this study was to analyze the processes of social cognition on the background of a wide range of other neuropsychological variables in patients with various psychiatric diagnoses. The study was established to answer the question about the specificity of the mental states recognition and interpretation and the possible relationship of these processes with the executive functions and other cognitive processes. Material and methods: There were studied two patients: one with a diagnosis of schizophrenia, the other with a diagnosis of bipolar affective disorder. A battery of a various neuropsychological tools was used to clinical assessment including the measurement of social cognition processes. Patients were also examined with auditory event related potentials (ERP) and global assessment of social functioning. Results: Patients vary in a range of variables: patient with schizophrenia obtained better results at neuropsychological tests exploring executive functions and learning of verbal material. The ERP study also revealed significantly higher amplitude of the N200 and P300b in this patient. At the same time, patient with bipolar disease had better results in the area of social cognition. Conclusions: 1 There is a dissociation between social cognition and executive functions and other cognitive processes. 2. Measurement of social cognition may be useful in differentiating patients with schizophrenia and bipolar disorder. 3. It seems reasonable to create a properly prepared neuropsychological rehabilitation training for patients with different diagnoses. 4. Precise measurement of social cognition effectiveness is likely to enable more accurate, than the general psychological assessment, predicting the level of social functioning in patients with selected neuropsychiatric disorders.